On theories and estimation techniques of fiscal multipliers - Sebastian Gechert (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2017)
The fiscal multiplier is a condensed key figure of the complex transmission mechanism of fiscal policy into output. I give an overview and systemize the numerous contributions to the theory and measurement of multipliers. The analysis is not confined to a certain model class but is intended to be as inclusive as possible to lay out the relevant channels of influence that have been discussed in the literature, while pointing to some blind spots. I also review the econometric problems when estimating fiscal multipliers and the estimation techniques at hand.
Keywords: B00; E62; 330; Fiscal multiplier; literature review; history of economic thought